Efficacy of Locally Administered 1.2% Rosuvastatin Gel in Patients with Periodontitis: A Randomized Placebo Controlled Clinical Trial - Chatterjee, Debopriya; Kapoor, Anjali; Vijay, Sharmistha; Sobti, Geetika; Kara, Dheeraj; Thanvi, Jaishree (European Journal of Dentistry, 2019)
Objective Periodontitis initiation and progression are a result of host immune inflammatory response to oral pathogens. Several pharmacological agents are being delivered locally, to improve periodontal health. Hence, the present randomized placebo controlled clinical trial is designed to check the clinical and antimicrobial efficacy of locally delivered 1.2% rosuvastatin (RSV) in intrabony defects (IBD) in periodontitis patients.Materials and Methods One-hundred patients were randomly allotted into two treatment groups: group A received 1. 2% RSV gel, scaling and root debridement and group B received placebo gel, scaling and root debridement. Clinical parameters, including modified sulcus bleeding index (mSBI), probing depth (PD), clinical attachment level (CAL), and plaque index (PI), were recorded at baseline before phase 1 and after 6 months. Radiographic assessment of IBD was done by cone beam computed tomography at baseline and after 6 months. Anaerobic colony count was done at baseline and after 180 days.Results On intragroup comparison, there is a significant improvement in periodontal parameters in both the groups. On intergroup comparison, there is significant gain in CAL in group A than group B (p = 0.04). There is significant decrease in PD in group A, compared to group B. There is significant bone fill in group A (p = 0.034), compared to group B. With respect to mSBI, PI, and anaerobic colony count, there is no significant difference between the two groups after 6 months. No adverse effect was noticed in any subjects.Conclusion The author concludes that 1.2% RSV gel when delivered locally into IBD improved periodontal clinical parameters such as PD and CAL and showed significant bone fill.
Keywords: bone loss; inflammation; periodontitis; statins